(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
For many years, heritage studies have devoted their attention to abstract cultural values. However, knowledge of the economic value of the heritage on which investment decisions are based on preservation projects has become available, especially with the development of conservation economics, which is one of the new fields that benefit from the language of the economy as one of the basic concepts in our lives. In general, and its development in the field of preservation, especially. The research problem was: "Lack of literature, especially Arabic, which discusses investment and its potential in projects to preserve urban heritage". The research is based on the hypothesis that "investment directed at urban heritage conservation projects can contribute to the financing required by these projects, as well as contribute to the development of local communities." The research aims at: "Building the theoretical base of the concepts of investment in projects to preserve urban heritage, and indicating the potential of investment provided by the urban heritage, and then the role of investment in preserving the heritage and development activities on the urban and social levels." For the purpose of achieving the objective of the research and test hypothesis, the research included two main approaches. The first: the potential investment of urban heritage, and the second: the experiment of the Aga Khan Foundation in the Azhar Park project as a case study. The research concludes with number of conclusions and recommendations, the main conclusion being: Reuse and tourism (internal and external) represent the main investment potential in conservation projects.